Uncovering the approach to develop ultra-high performance concrete (UHPC) with dense meso-structure based on rheological point of view: Experiments and modeling. (15th February 2021) - Yu, Rui; Zhou, Fengjiao; Yin, Tianyi; Wang, Zhiyu; Ding, Mengxi; Liu, Zhen; Leng, Yong; Gao, Xu; Shui, Zhonghe
Highlights: An efficient method to develop UHPC with dense meso structure is proposed; Herschel-Bulkley Model is more suitable to describe fresh UHPC; There is an optimal viscosity range for fresh UHPC to eliminate air bubbles; The dynamic modeling of trapped air bubble in fresh UHPC is presented; The rheology, particle packing etc. should be simultaneously considered. Abstract: This study is aiming to propose an optimized design method for Ultra-High Performance Concrete (UHPC) with dense meso -structure based on rheological point of view. Firstly, a UHPC particle packing skeleton is designed based on particle close packing model. Then, the dynamic modeling of air bubbles in fresh UHPC is executed based on Stokes's law, which is also used to clarify the appropriate UHPC rheological model. After that, the effect of superplasticizer and supplementary cementitious materials (SCMs) on the UHPC rheological characteristics are evaluated and discussed. The obtained results show that the Herschel-Bulkley model is more suitable to be utilized to describe the rheological properties of sticky UHPC in fresh state. Besides, there is an optimized viscosity range in the fresh UHPC, in which the trapped air voids can easily escape without vibration. In practice, based on a multiply consideration of rheological characteristics, particle packing skeleton and chemical functional admixtures, a UHPC with advanced mechanical properties and dense meso -structure could be efficiently developed.